FAMILY COMMUNICATION ON SINGLE MOTHER FAMILIES - Lucy Pujasari Supratman (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2018)
The data of divorce by women is increasingly today. There are at least 553 divorce cases registered to Bandung Religious Court in 2017 – most of them was proposed by women. This research wants to describe the form of family communication done by single mothers to their teenagers as a single parent. The method of this research is qualitative with case study approach. The researcher interviewed five single mothers lived in Bandung. The result shows that interpersonal communications on all informants were divided into coercive and democratic communication. The democratic communication is the most effective communication form to build a strong bond with the teenagers in a new single family. The contribution of this research is providing a new model of interpersonal coercive communication.